Effect of the Number of Benzene-Ring, the Functional Groups and the Absorbent Material on the Performance of Pt Nanoparticles Supported on Modified Graphite Nanoplatelet. (20th January 2015) - Zhu, Yanxia; Li, Zhejun; Huang, Chengde; Wang, Yuxin
Abstract: A graphite nanoplatelet (GNP) modified with small organic molecules and inorganic element was prepared and subsequently used as an electrocatalyst for the electrooxidation of methanol. The Pt/modified-GNP composite catalyst was characterized by Raman spectrometer, X-ray diffraction, transmission electron microscopy and X-ray photoelectron spectroscopy. The electrochemical properties and electrocatalytic activities of the Pt/modified-GNP hybrid were evaluated by cyclic voltammetry and chronoamperometry. The results indicate that the number of benzene-ring in the organic molecules and the identity of the inorganic elements can influence the dispersion of the Pt nanoparticles. Combine the inorganic elements with aminopyrene (amin) improved the activity of the resultant catalysts for methanol electrooxidation. The activity of the catalysts exhibits an order of Pt/Sn-amin-G < Pt/Ce-amin-G < Pt/Al-amin-G.